Lowering DNA binding affinity of SssI DNA methyltransferase does not enhance the specificity of targeted DNA methylation in E. coli - Krystyna Ślaska-Kiss (Nature Portfolio, 2021)
Abstract Targeted DNA methylation is a technique that aims to methylate cytosines in selected genomic loci. In the most widely used approach a CG-specific DNA methyltransferase (MTase) is fused to a sequence specific DNA binding protein, which binds in the vicinity of the targeted CG site(s). Although the technique has high potential for studying the role of DNA methylation in higher eukaryotes, its usefulness is hampered by insufficient methylation specificity. One of the approaches proposed to suppress methylation at unwanted sites is to use MTase variants with reduced DNA binding affinity. In this work we investigated how methylation specificity of chimeric MTases containing variants of the CG-specific prokaryotic MTase M.SssI fused to zinc finger or dCas9 targeting domains is influenced by mutations affecting catalytic activity and/or DNA binding affinity of the MTase domain. Specificity of targeted DNA methylation was assayed in E. coli harboring a plasmid with the target site. Digestions of the isolated plasmids with methylation sensitive restriction enzymes revealed that specificity of targeted DNA methylation was dependent on the activity but not on the DNA binding affinity of the MTase. These results have implications for the design of strategies of targeted DNA methylation.